Effects of dietary n-3 fatty acids on oxidative metabolism of bobwhite quails - Nagahuedi, Simba (University of Ottawa (Canada), 2009)
Lipids are believed to be the major fuel used during non-stop flights in migrant bird species, and potential mechanisms that enhance the capacity for fatty acid utilization have been identified in migrant birds. One of these adjustments is the use of dietary lipids, such as n-3 eicosapentaenoic (EPA) and docosahexaenoic acid (DHA), as performance-enhancing substances. Recently, these fatty acids have been found to improve the oxidative capacity of wild semipalmated sandpipers (Calidris pusilla) just prior to their migration to South America, by increasing the activity of the Krebs cycle and beta-oxidation enzymes. However, these experiments were conducted in a "natural context" and consequently it is impossible to control for a number of confounding variables (such as seasonal migration effects) that could also affect oxidative enzymes independent of diet. Therefore, this thesis aimed to investigate the effects of the diet on Krebs cycle and beta-oxidation enzymes using captive bobwhite quails (Colinus virginianus) as a model, while also attempting to elucidate the potential mechanisms of action. My goal was to characterize the roles of EPA and DHA in stimulating oxidative capacity, either through changes in membrane composition or through activation of peroxisome proliferator-activated receptors (PPARs). Birds received the following dietary treatments for 6 weeks: EPA, DHA or EPA+DHA. Following the experimental treatments, the activity of several enzymes was measured in quail flight muscles including Krebs cycle enzymes such as citrate synthase and cytochrome oxydase (respectively CS, COX); and markers for beta-oxidation such as carnitine palmitoyl transferase and 3-hydroxyacyl dehydrogenase (respectively CPT and HOAD), as well as the expression of PPAR genes. Results reveal that dietary n-3 fatty acids stimulated the activity of oxidative enzymes by 58-90%; surprisingly increases such as these are found only in extreme regimes of endurance training. Moreover, sedentary quails showed the same changes in membrane composition as refueling sandpipers. EPA and DHA have shown similar doping effects, possibly because the two fatty acids are easily interconverted. The substitution of n-6 arachidonic acid (ARA) by dietary n-3 fatty acids in membrane phospholipids plays an important role in mediating the metabolic effects of the diet, but results provide no significant support for the involvement of PPARs (as determined by changes in gene expression). This study also demonstrates that modifications in fatty acid composition of mitochondrial and sarcoplasmic reticulum membranes can be assessed by monitoring total muscle phospholipids, because all phospholipids are equally affected by diet. Overall the dietary n-3 fatty acids stimulate the capacity for aerobic metabolism in quail flight muscles, thereby mimicking the natural doping effects previously reported in wild sandpipers. However, the absence of associations between the activity of some enzymes and membrane composition is strong evidence that PPARs could be involved in the stimulation of oxidative capacity.
Keywords: Biology, Physiology.